2021
DOI: 10.1029/2021rs007286
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the New Background Covariance Model for the Ionospheric Data Assimilation

Abstract: This paper presents the evaluation of the recently developed covariance model for the Ionospheric Data Assimilation Four-Dimensional (IDA4D) technique. The ionospheric data are generated using the Observation System Simulation Experiment Tool from the known ionospheric state produced by the physics-based Thermosphere-Ionosphere-Mesosphere Electrodynamics General Circulation Model. Several experiments are conducted to assess performance of IDA4D with data-driven vertical and horizontal covariance matrices. We s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 17 publications
0
25
0
Order By: Relevance
“…Forsythe et al. (2020, 2021) constructed global maps of ionospheric correlation lengths and developed new background covariance models for ionospheric data assimilation. These avenues provide a useful step toward improving the specification of background error covariance. Devising high‐precision regional data assimilation schemes to specify detailed localized ionospheric weather features: Most current ionospheric data assimilation models have been built to run on a global scale that may not always have optimal performance in representing local mesoscale ionosphere morphology.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Forsythe et al. (2020, 2021) constructed global maps of ionospheric correlation lengths and developed new background covariance models for ionospheric data assimilation. These avenues provide a useful step toward improving the specification of background error covariance. Devising high‐precision regional data assimilation schemes to specify detailed localized ionospheric weather features: Most current ionospheric data assimilation models have been built to run on a global scale that may not always have optimal performance in representing local mesoscale ionosphere morphology.…”
Section: Introductionmentioning
confidence: 99%
“…Forsythe et al. (2020, 2021) constructed global maps of ionospheric correlation lengths and developed new background covariance models for ionospheric data assimilation. These avenues provide a useful step toward improving the specification of background error covariance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior work from (Forsythe, Azeem, Blay, et al, 2021) found similar structure in the vertical correlation length in that the correlation length increases with altitude and is typically between 50 and 200 km, however they do not use a 200 km limit so their high altitude correlation lengths are much larger. Our use of exclusively bottomside ionosonde data also contributes to this difference.…”
Section: Vertical Correlationmentioning
confidence: 81%
“…This is because of the influence of horizontal correlation lengths from nearby GPS stations over southern Europe (Figures 2a–2d). In fact, IDA4D NmF2 results over mid‐latitude are more accurate than IRI NmF2 (V. V. Forsythe et al., 2021; Jeong et al., 2022; Mengist et al., 2019). The accuracy of IDA4D F2 peak density altitude (hmF2) is not discussed in this study because assimilating GPS‐STEC or GPS‐STEC and C2 NmF2 (Figure 4) has little or no effect on IRI hmF2 improvement (Ssessanga et al., 2019).…”
Section: Results and Validationmentioning
confidence: 99%